Diclofenac removal from waste water by UV-A LED-based heterogeneous photocatalysis - Trousil, Vojtěch; Palarčík, Jiří; Smolný, Marek; Blažková, Zuzana; Machalický, Oldřich; Cakl, Jiri (University of Pardubice, 2019)
Degradation of the active pharmaceutical ingredient diclofenac (DCL) was studied using a laboratory-scale photoreactor equipped with highly efficient UV-A LEDs. Three photocatalysts (Aeroxide P25, Hombikat UV 100 and Precheza AV01) were tested and compared. In addition to deionized water, the other types of water (water matrices), were then tap water, unfiltered surface water, and the primary effluent of a wastewater from the municipal treatment plant. The experimental results indicated that the UV-A LED source operating at a wavelength of 368 nm had been much more efficient when combined with Precheza AV-01 photocatalyst of the microstructured anatase type. A negligible contribution of photolysis was noticed, while UV-A/TiO2 photocatalysis was more efficient in DCL removal in both the tap and the surface water matrices. The removal rate of DCL from the wastewater matrix was more dependent on the matrix itself than on the chemical structure of the micropollutant. The addition of hydrogen peroxide to the photocatalytic system enhanced the removal rates. The results of the algal growth inhibition test revealed a significant reduction of toxicity to Parachlorella kessleri after UV-A LED irradiation of the DCL solution. In addition, the reduction of the 'matrix toxicity' was also observed.
Keywords: diclofenac; photocatalytic degradation; UV-A LEDs; wastewater